The Effect of Organizational Ambidexterity, Innovation Capability and Leadership Competencies On Business Peformance Mediated Competitive Advantage In Software House Industry Employees In Indonesia - Triyani, Triyani; Usman, Bahtiar; Aseanty, Deasy (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to find out the effect of organizational ambidexterity, innovation capability and leadership competencies on business peformance mediated competitive advantage. In order to maintain business continuity, the software house must be able to improve its business performance. While previous research identified factors that impact business performance in various sectors, this study focuses on how internal organizational factors are in the software house. This study uses a quantitative approach, where the variables to be observed are quantified through an operational definition process. Data of 540 respondents was collected from 18 large-scale software in Indonesia. There are 10 hypotheses developed and tested using structural equation modeling. The results showed that organizational ambidexterity, innovation capability and leadership competencies had a significant effect on business performance and competitive advantage showed a positive and significant mediation influence in the model. The results also provide specific measurement of competitive advantage in the software house industry, managerial implications and suggestions for further research.